Psoriasis uncovered – measuring burden of disease impact in a survey of Australians with psoriasis. (4th February 2013) - Baker, Chris S; Foley, Peter A; Braue, Anna
Abstract: Background/Objectives: Internationally, the understanding of psoriasis has advanced in recent years to the point now where it is no longer considered a benign or cosmetic skin condition but a systemic, immune‐mediated disease associated with significant comorbidities and considerable detriment to quality of life. The aim of this study was to gain a better understanding of the physical, psychosocial and medical burden of psoriasis on Australian adults and the impact on health status. Methods: Two large‐scale multi‐centre cross‐sectional studies of Australian adults with psoriasis were conducted during 2010 and 2011, with the participation of a national patient representative group (Psoriasis Australia). The studies were based on detailed questionnaires that were self‐completed by individuals with psoriasis. Results: A total of 362 and 330 completed surveys were received in 2010 and 2011, respectively. A significant physical, psychosocial and medical burden was reported by the respondents. It was noteworthy that patients reported actively concealing their disease from the general public (83%), work colleagues (65%), friends (58%), employers (49%), family (40%), close friends (39%) and spouse/partner (20%). The mean five‐dimension European quality of life (EQ‐5D) score for the 2011 cohort was 0.73, representing a significant impact on their HRQoL. The presence of comorbidities, found in three‐quarters of the cohort, was associated with an even greater detriment to their HRQoL (mean score 0.64). Conclusions: Psoriasis imposes a significant psychosocial burden on the lives of patients, including a profound impact upon their personal and professional relationships, social interactions and quality of life, to a degree comparable to other serious chronic conditions. This study highlights the importance of collaboration between primary and specialist health‐care providers in developing patient management strategies that address the spectrum of physical and psychological manifestations associated with psoriasis.